The Role Of Job Satisfaction In Mediating Organizational Culture And Motivation On Organizational Commitment Of Contract Midwives. - Abrori, Imam; Darmawan, Kusnanto; Wibisono, Wimbo (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Early efforts are needed to realize the next generation of a quality nation. Midwives are one of the parties who play an important role in realizing this. This study aims to examine the effect of motivation and organizational culture on organizational commitment through job satisfaction in contract midwives in Jember Regency. The research design used is explanatory research. The population of this study were all contract midwives in Jember Regency, totaling 149 people. The sample taken was 112 respondents using purposive sampling technique with a quota sampling approach. The analytical tool used is Structural Equation Modeling (SEM). Stages of data testing in this study through validity, reliability, Structural Equation Modeling, hypothesis testing, interpretation and model identification. The model used in this study as a whole is good enough because it has met 7 of the 8 Goodness of Fit measurements. The results of this study prove that motivation has a significant positive effect on job satisfaction and organizational commitment. Organizational culture has a significant positive effect on job satisfaction and organizational commitment. Job satisfaction has a significant positive effect on organizational commitment, and job satisfaction has a positive effect in mediating motivation and organizational culture on organizational commitment.